A homozygous hypomorphic BNIP1 variant causes an increase in autophagosomes and reduced autophagic flux and results in a spondylo‐epiphyseal dysplasia. Issue 5 (21st March 2022) - Holling, Tess; Bhavani, Gandham S.; von Elsner, Leonie; Shah, Hitesh; Kausthubham, Neethukrishna; Bhattacharyya, Shaila S.; Shukla, Anju; Mortier, Geert R.; Schinke, Thorsten; Danyukova, Tatyana; Pohl, Sandra; Kutsche, Kerstin; et al.
Abstract: BNIP1 (BCL2 interacting protein 1) is a soluble N‐ethylmaleimide‐sensitive factor‐attachment protein receptor involved in ER membrane fusion. We identified the homozygous BNIP1 intronic variant c.84+3A>T in the apparently unrelated patients 1 and 2 with disproportionate short stature. Radiographs showed abnormalities affecting both the axial and appendicular skeleton and spondylo‐epiphyseal dysplasia. We detected 80% aberrantly spliced BNIP1 pre‐mRNAs, reduced BNIP1 mRNA level to 80%, and BNIP1 protein level reduction by 50% in patient 1 compared to control fibroblasts. The BNIP1 ortholog in Drosophila, Sec20, regulates autophagy and lysosomal degradation. We assessed lysosome positioning and identified a decrease in lysosomes in the perinuclear region and an increase in the cell periphery in patient 1 cells. Immunofluorescence microscopy and immunoblotting demonstrated an increase in LC3B‐positive structures and LC3B‐II levels, respectively, in patient 1 fibroblasts under steady‐state condition. Treatment of serum‐starved fibroblasts with or without bafilomycin A1 identified significantly decreased autophagic flux in patient 1 cells. Our data suggest a block at the terminal stage of autolysosome formation and/or clearance in patient fibroblasts. BNIP1 together with RAB33B and VPS16, disease genes for Smith‐McCort dysplasia 2 and a multisystem disorder with short stature, respectively, highlight the importance of autophagy in skeletal development. Abstract : In this study, we identified the homozygous BNIP1 intronic variant c.84+3A>T to cause a spondylo‐epiphyseal dysplasia in two probands. Our functional studies demonstrate an increased number of lysosomes in the cell periphery with normal lysosomal motility, an accumulation of autophagosomes, and reduced autophagic flux in patient‐derived fibroblasts.